2010
DOI: 10.1074/jbc.m109.070037
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor GATA4 Inhibits Doxorubicin-induced Autophagy and Cardiomyocyte Death

Abstract: Doxorubicin (DOX) is a potent anti-tumor drug known to cause heart failure. The transcription factor GATA4 antagonizes DOX-induced cardiotoxicity. However, the protective mechanism remains obscure. Autophagy is the primary cellular pathway for lysosomal degradation of long-lived proteins and organelles, and its activation could be either protective or detrimental depending on specific pathophysiological conditions. Here we investigated the ability of GATA4 to inhibit autophagy as a potential mechanism underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
200
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(217 citation statements)
references
References 61 publications
14
200
0
3
Order By: Relevance
“…Sishi et al reported that upregulation of autophagy protected against DOXinduced cardiotoxicity [16]. In contrast, DOX-induced cardiomyocyte death was aggravated by the activation of autophagy but attenuated by the inhibition of autophagy through GATA4 gene silencing, suggesting that excessive autophagy contributes to DOX-induced cardiotoxicity [35]. Thus, the role of autophagy in DOX-induced cardiotoxicity is still controversial because autophagy plays roles in both cell protection and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Sishi et al reported that upregulation of autophagy protected against DOXinduced cardiotoxicity [16]. In contrast, DOX-induced cardiomyocyte death was aggravated by the activation of autophagy but attenuated by the inhibition of autophagy through GATA4 gene silencing, suggesting that excessive autophagy contributes to DOX-induced cardiotoxicity [35]. Thus, the role of autophagy in DOX-induced cardiotoxicity is still controversial because autophagy plays roles in both cell protection and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In promoting cell death, oxidative stress from ROS, including superoxide and peroxynitrite, cause activation of kinase pathways (MAPK 4/7, checkpoint kinase 2, stress‐activated protein kinase, JNK). Suppression of transcription factors, GATA‐4 (Kobayashi et al ., 2010; Suzuki, 2011) and p300 (Poizat et al, 2005), is also linked to regulation of cell survival. Induction of small heat shock proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Adenoviruses expressing β-galactosidase (Ad β-gal), human BECN1 (AdBCN1), the shRNA targeting rat BECN1 mRNA (AdshBCN1), and control shRNA (AdshCon) were created as previously described. 68 Adenovirus expressing mTOR and adenovirus encoding mRFP-GFP tandem fluorescent-tagged LC3 (AdtfLC3) were the gifts of Dr. Chris Rhodes 56 and Dr. Junichi Sadoshima, 46 respectively. To generate adenoviral vector expressing ATG7, an insert containing Atg7 cDNA sequence was amplified by PCR from mycand flag-tagged ORF clone of Mus musculus Atg7 (OriGene, MR210108) and integrated into the TA cloning vector (Invitrogen, KNM2000-01).…”
Section: Methodsmentioning
confidence: 99%
“…Protein extracts from cultured cardiomyocytes were prepared as described previously, except that 1% of protease inhibitor cocktail (Sigma, P8340) was added to the extraction buffer. 68 Protein samples were subjected to PAGE, transferred to polyvinylidene difluoride membrane (Amersham Pharmacia, RPN3031 or Bio-Rad, 162-0177), and then blocked in 5% milk prepared with 0.1% Tween-20 Tris-buffered saline (TBST) solution for 1 h at room temperature. Primary antibodies were incubated overnight at 4°C in 2.5% milk.…”
Section: Methodsmentioning
confidence: 99%